Ethnics in Expressing Opinions on Social Media: The Role of Regulation, Influence of Public Opinio, Legal Awareness, Online Security, and Social Responsbility Convolutional Neural Network Method - Muhammad Caesar Akbar; Alamda Zeki Amala (Jurnal Multidisiplin Sahombu, 2025)
Social media has become a major platform for public opinion. However, this freedom is often not accompanied by adequate ethical responsibility. This study highlights the case of "Poltekbang and the funding crisis" as a real example of how violations of communication ethics on social media can have a negative impact on the reputation of individuals and institutions. Using a phenomenological approach, this study explores various comments and narratives that develop on social media, accompanied by references from academic journals, including those indexed by Scopus. The results of the analysis show that the spread of information without a verification process, the emergence of hate speech, and the tendency to overgeneralize are the main patterns of ethical violations on social media. Based on these findings, this study recommends increasing digital literacy and implementing empathy-based communication guidelines. These steps are expected to encourage the creation of a healthier, more constructive, and more responsible discussion culture in the digital space.